Digital Demodulation Using I/Q Signals and Optical Phase Control Applied to a Vibrometer - Galvez-Limaco, Angel Manuel [UNESP]; Galeti, Jose Henrique; Nelli Silva, Emilio Carlos; Higuti, Ricardo Tokio [UNESP]; Connelly, Michael J.; Kitano, Claudio [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
An efficient and cost effective optical phase detection vibrometer based on a modified closed loop homodyne Michelson interferometer is presented. Real-time phase demodulation is carried out, using an embedded platform that performs data acquisition, signal processing, PI (proportional-integral) control and the generation of signals that drive the electrooptic Pockels cell phase shifter and the piezoelectric actuator under test. Two phase quadrature signals are generated from a single interferometric output, using the interleaving action, in alternation, of a digitally generated modulating signal, and then the well-known differential-cross-multiplication technique is applied to perform the computation of the phase shift of interest. The quadrature condition is reached using the PI loop based on an error signal obtained from a Lissajous figure derived from out-of-phase signals. The vibrometer is capable of measuring nanometric displacements, and is simple, inexpensive, accurate, immune to fading and self-consistent. The new method was used to determine the displacement frequency response curves of two prototypes of multi-actuated flextensional piezoelectric actuators. Measurements were made between 500 Hz and 15 kHz, and the results agreed with those obtained by the standard SCM-Signal Coincidence Method.
Keywords: Optical interferometry; Optical sensors; Laser beams; Adaptive optics; Piezoelectric materials; Semiconductor device measurement; piezoelectric transducers; signal processing; metrology